Studi Analisis Surat Kuasa Khusus (Tinjauan Konsep dan Asas Akad Hukum Islam) - Sopian S (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This paper is entitled the study of the analysis of special powers of attorney (a review of concepts and principles of Islamic law), revealing aspects of the concepts and principles contained in special powers of attorney which are analyzed with the concepts and principles of Islamic law. Special power of attorney is used as an alternative solution for people or legal entities that cannot carry out legal problems or interests for him who then represent to other parties to act legally on him. With an agreement between the giver and the recipient of the power of attorney, it will automatically bring up clauses as a guide and guide in legal action. The engagement that appears in Islamic law is known as aqad, if it is examined through aspects of Islamic law, it will bring up things that must be analyzed, namely the concepts and principles contained in the special power of attorney.